Fibrinogen Response to Turpentine and Endotoxin in Busulfan-Treated Rabbits - Rapaport, Samuel I.; Zivelin, Ariella (Thrombosis and Haemostasis, 1976)
The response of the plasma fibrinogen level to the subcutaneous injection of turpentine and to the intravenous injection of endotoxin was measured in normal rabbits and in rabbits made granulocytopenic and thrombocytopenic with busulfan. Plasma fibrinogen levels rose sharply in both normal and busulfan-treated rabbits but to a significantly lesser extent in the latter animals. A statistically significant relation was found between the number of residual granulocytes in busulfan-treated rabbits and the extent of the rise in fibrinogen level after turpentine. As discussed herein, these data are consistent with the hypothesis that material from granulocytes plays a pathophysiologic role in the stimulation of fibrinogen synthesis in inflammation and after tissue trauma.